Nutrition by Design: Boosting Selenium Content and Fresh Matter Yields of Salad Greens With Preharvest Light Intensity and Selenium Applications - Zhu, Xudong; Yang, Tianbao; Sanchez, Charles A.; Hamilton, Jeffrey M.; Fonseca, Jorge M. (Frontiers in Nutrition, 2022)
Selenium (Se) is an essential mineral in multiple human metabolic pathways with immune modulatory effects on viral diseases, including SARS-CoV-2 and HIV. Plant-based foods contain Se metabolites with unique functionalities for the human metabolism. In order to assess the value of common salad greens as Se source we conducted a survey of lettuce commercially grown in 15 locations across the USA and Canada and found a tendency for Se to accumulate higher (up to 10 times) in lettuce grown along the Colorado river basin region, where the country’s highest amount of annual solar radiation is recorded. In the same area, we evaluated the effect of sunlight reduction on the Se content of two species of arugula (Eruca sativa cv. ‘Astro’ and Diplotaxis tenuifolia cv. ‘Sylvetta’). A 90% light reduction during the 7 days before harvest resulted in over 1/3 Se decline in D. tenuifolia. The effect of light intensity on yield and Se uptake of arugula microgreens was also examined under indoor controlled conditions. This included High intensity (HI, 160 µ mol m-2 s-1 for 12 h/12 h light/dark), Low intensity (LI, 70 µ mol m-2 s-1 for 12 h/12 h light/dark) and High Intensity plus UV-A (HI-UVA, 12h light of 160 µ mol m-2 s-1, 2h UV-A of 40 µ mol m-2 s-1 and 10 h dark) treatments in a factorial design with 0, 1, 5 and 10 ppm Se in the growing medium. HI and HI-UVA produced D. tenuifolia plants with 25 to 100% higher Se content than LI, particularly with the two higher Se doses. The addition of Se produced a marked increase in fresh matter (>35% in E. sativa and >45% in D. tenuifolia). This study i) identifies evidence to suggest the revision of food composition databases to account for large Se variability, ii) demonstrates the potential of introducing pre-harvest Se to optimize microgreen yields, and iii) provides the controlled environment industry with key information to deliver salad greens with targeted Se contents.